Melanoma - Lasfar, Ahmed; Cohen-Solal, Karine (IntechOpen, 2021)
Although melanoma represents a limited number of cutaneous cancers each year, it remains a significant public health crisis because the metastatic disease is associated with poor survival. The incidence of the disease has increased 200% since 1973 and the median age at diagnosis is 40 years, making it one of the most significant cancers responsible for productive years of life lost. Fortunately, there has been unprecedented progress in the treatment of advanced melanoma, largely through advances in understanding how to manipulate immune responses and target selective genetic mutations in melanoma patients. Clinical benefits to patients with advanced melanoma have been nevertheless limited by the development of innate and acquired drug resistance, and numerous efforts are focusing on the elucidation of these mechanisms. Combination strategies are being actively investigated to overcome drug resistance, by awakening existing anti-tumor mechanisms disabled by a cancer-promoting microenvironment. This book explores the advances and challenges associated with melanoma today, particularly those related to its diagnosis and management. It also proposes new avenues for therapeutic opportunities based on sustained research efforts and ever-growing technological advances. This is a relevant source of knowledge, very useful for researchers, medical doctors, health providers and all individuals interested in learning more about this devastating disease.